Differences in serum proteins in traditional Chinese medicine constitutional population: Analysis and verification. Issue 2 (5th April 2020) - Tan, Fei; Chen, Xinyan; Zhang, Huihua; Yuan, Jiamin; Sun, Chen; Xu, Fuping; Huang, Li; Zhang, Xiaoxuan; Guan, Huahua; Chen, Ziwen; Wang, Chen; Fan, Shaoyi; et al.
Abstract: Traditional Chinese medicine assigns individuals into different categories called "constitutions" to help guide the clinical treatment according to subjective physiologic, psychologic analyses, large‐scale clinical observations, and epidemiologic studies. To further explore more objective expressions of constitutions, antibody microarrays were used to analyze the serologic protein profiles of two different constitutions, a balanced (or healthy) constitution (BC) and the dampness constitution (DC) comprising phlegm‐dampness and damp‐heat constitutions. The profiles of changing constitutions across time were also analyzed. Nineteen differentially expressed proteins between the two groups were identified, with known biologic functions involved in immunity and inflammation. This proteomic study may provide a biologic explanation why the BC is different than the dampness constitution. Abstract : Proteomic analyses of serum using antibody microarrays reveal unique protein profiles between balanced and dampened "constitutions" in traditional Chinese medicine (TCM).